The use of enteral nutrition in pediatric patients with Crohn's disease - Bartosz Rudzki; Agnieszka Żwirełło; Grzegorz Burdyn; Karolina Leokadia Kaźmierczak- Siedlecka; Ewelina Lubieniecka-Archutowska; Anna Lebiedzińska (Polish Pharmaceutical Society, 2020)
Crohn's disease belongs to the group of inflammatory bowel disease and is characterized by inflammatory changes that can affect all part of the gastrointestinal tract. The etiology of Crohn's disease includes genetic background as well as environmental factor, such as diet (for instance, consumption of sugar, milk, and gluten). The disease progresses with periods of progression and remission. Inflammation often occurs in one part of gastrointestinal tract, however, usually involves several distant sections of the gastrointestinal tract. The complex therapy for Crohn's disease should include pharmacotherapy and nutritional treatment. Pediatric patients may have specific nutritional deficiencies depending on the gastrointestinal tract affected. When lesions are located in the distal part of the ileum, vitamin B12 deficiency may occur. Besides vitamin B12 deficiency, iron, folic acid, and magnesium deficiency may also be developed. The assessment of nutritional status of patients with Crohn's disease seems to be important due to identification of patients suffering from malnutrition or being at risk of malnutrition development. If the protein-caloric demand is not covered, the oral nutrition should be supplemented using oral nutritional supplements (ONS) and other oral food supplements. Enteral nutrition, which is given via artificial access to the alimentary tract, should be included in children with active Crohn's disease, when oral nutrition with oral nutritional supplements does not cover the quantitative and qualitative demand of the body. The efficiency of enteral nutrition is similar to the effect provided by corticosteroids. There are available several types of enteral formula including also immunomodulatory components, such as glutamine. The aim of nutritional therapy is to improve the patients' nutritional status and to achieve disease remission and its maintenance. The introduction of appropriate nutritional treatment prevents the occurrence of a deficiency of nutrients, minerals, and vitamins, and as a consequence supports the appropriate growth and development of the child.